ANALISIS PENYEBAB KETERLAMBATAN PENGADAAN MATERIAL PADA STASIUN X - Wahono, Dimas; Prabowo, Andy (Prodi Sarjana Teknik Sipil, FT, Universitas Tarumanagara, 2024)
This research aims to analyze the factors contributing to material procurement delays in the construction project of Station X. Delays in material procurement can have serious implications for project progress and budgets. Therefore, a profound understanding of the factors influencing these delays is crucial for enhancing construction project efficiency. This study employs factor analysis to evaluate historical data on material procurement in previous projects. The analyzed data include sudden order changes, material re-deliveries, and shifts in material requirements. The results of the factor analysis indicate that the most dominant factor influencing the risk of delays is